# Solve the inequality -2x-10(x-3)+3x%6(x-3)+9

## {3x-2x-10\left(x-3\right)}\geq {6\left(x-3\right)+9}

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$x\leq \frac{13}{5}$

## Step by step solution

Problem

${3x-2x-10\left(x-3\right)}\geq {6\left(x-3\right)+9}$
1

Multiply $\left(x+-3\right)$ by $-10$

$-2x+3x+30-10x\geq 9-18+6x$
2

Subtract the values $9$ and $-18$

$-2x+3x+30-10x\geq 6x-9$
3

Adding $3x$ and $-2x$

$30-10x+x\geq 6x-9$
4

Adding $-10x$ and $x$

$30-9x\geq 6x-9$
5

Grouping terms

$-6x+30-9x\geq -9$
6

Adding $-9x$ and $-6x$

$30-15x\geq -9$
7

Moving the term $30$ to the other side of the inequation with opposite sign

$-15x\geq -9-30$
8

Subtract the values $-9$ and $-30$

$-15x\geq -39$
9

Multiply both sides of the inequality by $-1$, reversing the sign

$15x\leq 39$
10

Divide both sides of the inequation by $15$

$x\leq \frac{13}{5}$

$x\leq \frac{13}{5}$

Polynomials

0.23 seconds

194